MODERASI KEPEMIMPINAN: HUBUNGAN TALENT MANAGEMENT DAN CULTURE ORGANIZATION TERHADAP PRODUKTIVITAS - Safar, Ilham; Meiliska, Alifia; Sari, Novita Kumala (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the role of leadership moderation in explaining the effect of talent management & culture organization on the productivity of PT. Sucofindo (Persero) Makassar Branch. The approach used in this study is a quantitative approach. The population in this study were employees of PT. Sucofindo (Persero) Makassar Branch with a total sample of 53 people. The technique used in data collection is a survey method in the form of a questionnaire which will then be processed in the SPSS application. The results showed that talent management has a negative and significant effect on employee productivity, culture organization has a very significant effect on employee productivity, and Talent Management and Culture Organization together have a positive and significant effect on the variable productivity of PT employees. Sucofindo Makassar Branch. The results of the study also showed that leadership was unable to strengthen the effect of talent management on employee productivity, and leadership was unable to strengthen the effect of culture organization on the productivity of PT employees. Sucofindo Makassar Branch.